Association of elevated blood pressure and impaired vasorelaxation in experimental Sprague-Dawley rats fed with heated vegetable oil - Leong, X.F.; Mustafa, Mohd Rais; Das, S.; Jaarin, K. (BioMed Central, 2010)
Background: Poor control of blood pressure leads to hypertension which is a major risk factor for development of cardiovascular disease. The present study aimed to explore possible mechanisms of elevation in blood pressure following consumption of heated vegetable oil.